TOXICITY TEST OF IRONWOOD BARK EXTRACT (Eusideroxylon zwageri) TOWARD WISTAR RATS KIDNEY (Rattus norvegicus) - Bimo Gondo Arum; I Wayan Arya Krishnawan Firdaus; Beta Widya Oktiani (FKG Unlam, 2023)
ABSTRACTBackground: The use of herbal medicinal plants by the community is increasing because the side effects are smaller than chemical-based drugs. One of the medicinal plants is ironwood because of its flavonoid and phenolic compounds which have the potential as antioxidants. Ironwood needs to be known for its toxicity, by performing an oral subchronic toxicity test on the kidneys of wistar rats with urea and creatinine parameters. Objective: Proving that the administration of ironwood bark extract at doses of 524.5 mg/mL, 1151.5 mg/mL, and 1775.5 mg/mL orally for 28 days had no toxic effect on the kidneys of wistar rats with parameters of urea and creatinine. Methods: Pure experimental research with posttest-only with control group design, consisting of 4 groups, each of which contained 4 wistar rats with 1 negative control group and 3 treatment groups given ironwood bark extract at a dose of 524.5 mg/mL, 1151, 5 mg/mL, and 1775.5 mg/mL. It was carried out for 28 days and on the 29th day the rats were taken blood and examined for urea and creatinine levels. Results: In the 3 treatment groups, urea values were 41, 42, and 32.35 mg/dL and creatinine was 0.725, 0.725, and 0.65 mg/dL and the results also showed that there was no significant difference in urea levels (p=0.076) and creatinine (p=0.076). 0.065) in each group. Conclusion: Ironwood bark extract dose 524.5 mg/mL, 1151.5 mg/mL, and 1775.5 mg/mL was not toxic to the kidneys of wistar rats with parameters of urea and creatinine. Keywords: Creatinine, Ironwood bark extract, Toxicity, Urea.